Penerapan Regulator Sebagai Pengaturan Tegangan Berbasis Internally Triggered Triac - Abdul Muis Prasetia; Nur Liya (Elektrika Borneo, 2021)
The development of science and technology has changed human civilization a lot. One of these technologies is control technology. Direct voltage source control is simple enough to be implemented by simply setting the voltage using a variable resistor. In contrast to the implementation in circuits with alternating current sources, a dimmer circuit is needed to control the voltage. Dimmer is an electronic circuit that modifies the form of a pure AC (Alternative Current) signal into a modulated signal so that the output voltage can be adjusted. The more complex dimmer uses PWM (Pulse Width Modulaion) as its controller. This PWM dimmer is able to produce a small power level, so that control becomes more precise. In this study, it was found that the application of a regulator as a voltage regulation based on internally triggered TRIAC with the application of the dimmer method. The results showed that the internally triggered TRIAC was able to control AC voltage well